The Difference in Parental Financial Socialisation Across Parental Education Level - Ndou, Adam (Research in Social Sciences and Technology- OpenED Network, 2024)
Around the world, parental financial socialization now heavily depends on the educational attainment of the parents. This study looked into how parental financial socialization varied depending on the educational attainment of the parents. Parental financial behavior, financial monitoring, financial discussion, financial communication, and financial teaching were used as metrics for measuring parental financial socialization. In this study, a quantitative research approach was used. Since Fetakgomo Tubatse and Intsika Yethu municipalities are the most rural and low-income locations in South Africa, data were gathered through the use of a self-administered questionnaire. Data analysis techniques included Tukey HSD test, Welch robust test, Levene's test, descriptive statistics, and exploratory factor analysis (EFA). The results demonstrated that parental financial socialization varies significantly depending on the educational attainment of the parents. Therefore, financial socialization is more common among parents who have greater education levels than it is among those who have lower education levels. This study's findings are the first to show that parental financial socialization varies significantly depending on the educational attainment of the parents. This study suggests that more research be done on the variations in parental financial socialization across parental educational levels in other areas. Additionally, it is advised that the South African government develop initiatives aimed at addressing and raising parental education levels because research indicates that parents who have completed more education are more likely to participate in financial socialization, which affects young adults' financial literacy and well-being.